Influence of Fissure Number on the Mechanical Properties of Layer-Crack Rock Models under Uniaxial Compression - Yun-liang Tan; Wei-yao Guo; Tong-bin Zhao; Feng-hai Yu; Bin Huang; Dong-mei Huang (Advances in Civil Engineering)
Many case studies have revealed that rock bursts generally occur in the high stress concentration area where layer-crack structures often exist, especially for brittle coal or rock masses. Understanding the mechanical properties of layer-crack rock models is beneficial for rational design and stability analysis of rock engineering project and rock burst prevention. This study experimentally investigated the influence of fissure number on the mechanical properties of layer-crack rock models through uniaxial compression tests. The digital speckle correlation method (DSCM) and acoustic emission (AE) techniques were applied to record and analyze the information of deformation and failure processes. Test results show the following: the bearing capacity of layer-crack specimen decreases compared with intact specimen, but their failure modes are similar, which are the splitting failure accompanied with local shear failure; the nonuniform deformation phenomenon begins to appear at the elastic deformation stage for layer-crack specimens; the AE behavior of intact specimens consists of three stages, that is, active stage, quiet stage, and major active stage, but for layer-crack specimens, it is characteristic by three peaks without quiet stage. In addition, as the fissure number of layer-crack specimens increases, the bearing capacity of specimens decreases, the appearing time of nonuniform deformation phenomenon in the specimen surface decreases, the AE events are denser and denser in each peak stage, and the risk of dynamic instability of layer-crack structure increases. At last, the failure mechanism of layer-crack structure and the related mitigation advices were discussed based on the test results. In general, the novelty is that this paper focuses on the failure mechanism of layer-crack structure directly.